ANALISIS KESULITAN SISWA SMP KELAS VIII PADA MATERI BANGUN RUANG SISI DATAR - Amsa Aulia Awwalin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of this research is to find out how the students' ability in the school in solving problems about building flat side spaces related to objects in the surrounding environment. The method used in this research is descriptive qualitative. Where the population to conduct this research is eighth grade students of junior high school in the district of West Bandung. The test instrument was in the form of problem statements consisting of 5 questions. The results of this study indicate that students of class VIII at the school have difficulty in solving questions about the material to build flat side space.